The 2nd International Electronic Conference on Remote Sensing 2018
DOI: 10.3390/ecrs-2-05160
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Historical Topography: Getting More from Archival Aerial Photographs

Abstract: High resolution elevation data is a fundamental information for multiple applications in geomorphology spanning from visual analyses to modeling. Nowadays, gathering of high-quality elevation data relies on multiple sensors and technologies which can be mounted on terrestrial, aerial and satellite platforms. In the last years, the Structure from Motion (SfM) algorithms have made possible the acquisition of high and very-high resolution elevation data from optical images acquired with high overlapping rates at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…One study [36] found Z error values (RMSE) varying between 0.50 to 0.91 m over two study sites and three different AP datasets. Another study [2] measured the RMSE in Z of 1.049 m, whereas [27] measured RMSE values in Z ranging between 2.11 and 1.98 m, analysing APs with resolutions of 800 and 1600 dpi over a complex topography. The uncertainty could be improved if a reliable and automatic method could be developed to remove the influence of vegetation from the DSM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study [36] found Z error values (RMSE) varying between 0.50 to 0.91 m over two study sites and three different AP datasets. Another study [2] measured the RMSE in Z of 1.049 m, whereas [27] measured RMSE values in Z ranging between 2.11 and 1.98 m, analysing APs with resolutions of 800 and 1600 dpi over a complex topography. The uncertainty could be improved if a reliable and automatic method could be developed to remove the influence of vegetation from the DSM.…”
Section: Discussionmentioning
confidence: 99%
“…Each photograph was scanned at 1200 dpi to obtain a high pixel resolution and to simplify ground control point (GCP) positioning and the surface matching during the SfM process. According to [27], the optimal scanning resolution to apply the SfM process on historical aerial photos is between 800 and 1600 dpi. The typical black border of archive aerial photographs was removed using a batch process in Adobe Photoshop [36].…”
Section: Historical Aerial Photographic Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…The computer vision techniques within SfM have allowed a qualitative improvement of the analysis by using much more of the information contained within the imagery to aid the orientation process, possibly unlocking large historical photogrammetric archives for morphologic analysis (Bakker and Lane, 2017). Recent examples of the application of the SfM technique using historical aerial photographs have been published for river/floodplain systems (Lane et al ., 2010; Bakker and Lane, 2017), mountainous and hilly areas (Gomez et al ., 2015; Seccaroni et al ., 2018), volcanic islands (Gomez et al ., 2015; Ishiguro et al ., 2016) and glaciers (Mölg and Bolch, 2017). However, as far as the authors know, no study has applied the technique to understand the morphodynamics of sandy beaches at decadal scale.…”
Section: Introductionmentioning
confidence: 99%
“…Structure from motion (SfM) [39] and bundle adjustment [40] introduced new ways of using scanned aerial photographs [41]. The use of such detectors as SIFT (scale-invariant feature transform) [42] or SURF [43] (speeded-up robust features), their modified versions, and the Random sample consensus (RANSAC) algorithm [44] which is used to identify photograph key points, facilitates relative orienting of blocks of historical photographs [45], despite the lack of data on the interior orientation or the distortion parameters of the lens [46].…”
Section: Introductionmentioning
confidence: 99%